VOC and CO Removals by Perovskite Type Nanocatalysts Supported on Commercial Substrates - Hosseinpour, Shahriar; Bahramgour, Mahsa; Hosseini, Seyyed Reza; Yildirim, Yılmaz; Niaei, Aligholi (Journal of Chemical Engineering Research Updates, 2021)
In this research, it was tried to choose a kind of perovskite catalyst with optimized formulation La0.8Sr0.2Co0.66Fe0.34O3 to remove air pollutants. This perovskite catalyst stabilized on the various supports such as alumina and ZSM-5 with the sol-gel synthesis technique and ceramic monolith by dip-coating method. Four different catalysts by variable weight percentage including PE-Al 10%, PE-Al 20%, PE-Al 30%, and PE-Al 40% were prepared by sol-gel synthesis technique. In this work, the XRD technique was used to confirm the formation of perovskite catalysts’ crystalline phases on the supports. As a result, XRD patterns revealed the formation of the perovskite phase onto the alumina and zeolite supports. Activity tests of these four catalysts were examined in the catalytic oxidation of Toluene and CO using an experimental setup consisting of a tubular flow reactor at the temperature 280-400°C and 100-400°C for the toluene and CO removal systems, respectively. According to the results of the catalysts’ activity test, the alumina supported with 40% w/w perovskite catalyst showed the best performance, and its activity was similar to the activity of the bulk catalyst (over 95% conversion of toluene at about 290°C). For the coated catalysts on a ceramic monolith, the complete removal of carbon monoxide at 50°C was lower than the powdered form. Results from the activity test in a toluene removal system that show coating of the bulk and supported catalysts on ceramic monolith; have an essential impact on the activity test of these catalysts.